Dual-wavelength operation in all-solid-state Cr:LiSAF lasers with grating-controlled coupled-cavities. (November 2015) - Kunpeng, Luan; Li, Yu; Yanlong, Shen; Chao, Huang; Feng, Zhu; Hongwei, Chen; Ke, Huang; Aiping, Yi
Abstract: An all-solid-state Cr:LiSAF laser with a grating-controlled coupled-cavity for dual-wavelength operation is demonstrated. One wavelength is decided by the main-cavity oscillation and fixed at 860 nm. The other wavelength can be tuned from 790 nm to 987 nm by the grating in the coupled cavity. The maximum output power is 10 mW and both the linewidths are narrowed to below 0.2 nm. Abstract : Highlights: Dual-wavelength emission in all-solid-state Cr:LiSAF lasers is demonstrated. Pump threshold decreases with external feedback. Dual-wavelength operation is achieved by adjusting the feedback ratio. With one wavelength fixed at 860 nm, the other one is tunable from 790 nm to 987 nm.